Rancang Bangun Prototipe Sistem Keamanan Gerbang Rumah Otomatis Menggunakan Nodemcu ESP8266 Dengan Kendali Telegram - Nishfahuddin, Ananda; Febriawan, Dimas (Journal of Information System Research (JOSH), 2024)
In an era of advancing technology, the need for smart and efficient home security systems is increasing. The problem addressed in this research is the lack of flexibility and effectiveness in conventional security systems, which still rely on physical involvement of homeowners and have limitations in providing diverse authentication methods. This research aims to design and develop a prototype of an automatic gate security system based on NodeMCU ESP8266, controlled via the Telegram application, as a solution to this problem. The system utilizes the AS608 fingerprint sensor for biometric authentication and a 4x4 keypad as an alternative input method. Users can remotely control the gate through Telegram, which also functions as a monitoring medium. The method used in this study involves the development of IoT-based hardware and software, along with the integration of multiple layers of authentication (biometric and PIN) to enhance security. The results of the study show that the system improves security by providing several reliable authentication methods. The system successfully integrates automatic gate control through text messages with fast response times. Evaluation indicates that the system functions as intended, with an average fingerprint sensor reading time of 102 seconds and a gate response time of 912 seconds. This system offers an effective solution for enhancing home security automatically and remotely.